2018
DOI: 10.1016/j.str.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Bicc1 SAM Polymer and Mapping of Interactions between the Ciliopathy-Associated Proteins Bicc1, ANKS3, and ANKS6

Abstract: Head-to-tail polymers of sterile alpha motifs (SAM) can scaffold large macromolecular complexes. Several SAM-domain proteins that bind each other are mutated in patients with cystic kidneys or laterality defects, including the Ankyrin (ANK) and SAM domain-containing proteins ANKS6 and ANKS3, and the RNA-binding protein Bicc1. To address how their interactions are regulated, we first determined a high-resolution crystal structure of a Bicc1-SAM polymer, revealing a canonical SAM polymer with a high degree of fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(62 citation statements)
references
References 49 publications
(115 reference statements)
5
53
0
Order By: Relevance
“…However, co-transfection of full length ANKS3 or of the truncated mutant ANKS3ΔC lacking the C-terminal region distal of its SAM domain inhibited CTLH complex binding to HA-Bicc1 ( Fig 6E ), indicating that ANKS3 competes with CTLH complex for Bicc1. Previous structure analysis suggests that the SAM domain of ANKS3 interfaces with the ML and EH surfaces of the Bicc1 SAM domain, thereby allowing the bulky C-terminal region of ANKS3 to block Bicc1 polymer elongation [ 41 ]. To distinguish whether ML or EH surfaces of the Bicc1 SAM domain or their oligomerization also mediate CTLH complex binding, we mutated them individually [ 19 ] ( S3 Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…However, co-transfection of full length ANKS3 or of the truncated mutant ANKS3ΔC lacking the C-terminal region distal of its SAM domain inhibited CTLH complex binding to HA-Bicc1 ( Fig 6E ), indicating that ANKS3 competes with CTLH complex for Bicc1. Previous structure analysis suggests that the SAM domain of ANKS3 interfaces with the ML and EH surfaces of the Bicc1 SAM domain, thereby allowing the bulky C-terminal region of ANKS3 to block Bicc1 polymer elongation [ 41 ]. To distinguish whether ML or EH surfaces of the Bicc1 SAM domain or their oligomerization also mediate CTLH complex binding, we mutated them individually [ 19 ] ( S3 Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…However, it may be relevant that Bicc1, a putative RNA-binding protein specifically expressed at the node of mouse embryos, is essential for L-R asymmetry. 65 ) Furthermore, Bicc1 interacts with ANKS3 and ANKS6, 66 , 67 ) and ANKS3 mutations have been identified in patients with laterality defects. 68 ) Finally, Bicc1 also binds to Cerl2 mRNA in zebrafish and thereby inhibits its translation.…”
Section: Symmetry Breaking At the L-r Organizermentioning
confidence: 99%
“…We observed that NPH members interact with BICC1, the mammalian homologue of the Drosophila bicaudal C (BicC) 15 , and detailed structural analysis confirmed the interaction of BICC1 with ANKS3 and ANKS6 19 . Required during Drosophila oogenesis to down-regulate oskar mRNA at the anterior pole 20 , BicC contains three conserved N-terminal K-homology (KH) domains responsible for RNA binding, and a C-terminal Sterile Alpha Motif domain (SAM), which recruits BICC1 into RNA-processing bodies (P-bodies) 21 .…”
Section: Introductionmentioning
confidence: 74%
“…BICC1 affects the localization of ANKS3 and ANKS6 19 . In the absence of hippuristanol, BICC1 recruited both proteins into TIA-1-negative granules, likely representing RNA-processing bodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation